MODEL PEMBINAAN RASA KEBANGSAAN MELALUI CITIZENSHIP EDUCATION PADA MASYARAKAT ENTIKONG WILAYAH PERBATASAN INDONESIA-MALAYSIA - Mardawani Mardawani; Agusta Kurniati (Universitas Negeri Malang, 2017)
Abstract: This study is motivated by the condition of West Kalimantan as one of the provinces whose territory is directly adjacent to the Malaysian state is often faced with a condition of society interacting with each other in the context of social life, economy and culture. The qualitative assessment method with case study type. The model of fostering nationalism through citizenship educationin Entikong society The border region of Indonesia Malaysia is a persuasive model by inviting the community to actively participate in the success of government programs Abstrak: Kajian ini dilatarbelakangi oleh kondisi Kalimantan Barat sebagai salah satu provinsi yang wilayahnya berbatasan langsung dengan negara Malaysia sering sekali dihadapkan pada suatu kondisi masyarakat yang saling berinteraksi baik dalam konteks kehidupan sosial, ekonomi maupun budaya. Metode pengkajian menggunakan kualitatif dengan jenis studi kasus. Model pembinaan rasa kebangsaan melalui citizenship education pada masyarakat Entikong Wilayah perbatasan Indonesia Malaysia adalah model persuasif dengan mengajak masyarakat berpartisipasi aktif mensukseskan program pemerintah DOI : http://dx.doi.org/10.17977/um019v2i12017p041